Buyers Credit Market in India - Singla, Akriti (2014)
The thesis is about the analysis of the current buyers credit market in India, its weaknesses and potential areas of improvements. It also deals with the idea of a new marketplace to replace the existing one and an evaluation of the new marketplace.